2022
DOI: 10.1002/jsfa.11782
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐diabetic and gut microbiota modulation effects of sacha inchi (Plukenetia volubilis L.) leaf extract in streptozotocin‐induced type 1 diabetic mice

Abstract: BACKGROUND Sacha inchi (Plukenetia volubilis L.) tea has been used as an adjuvant treatment for diabetes in Pu’er, in the Yunnan province of China. The effects of sacha inchi tea on diabetes and the underlying mechanisms remain unknown. This study was conducted to investigate the influence of a water extract of sacha inchi (P. volubilis L.) leaves (PWE) on hypoglycemic activity and gut microbiota composition in mice with streptozotocin (STZ)‐induced type 1 diabetes mellitus (T1DM). During the 6 weeks of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…According to published studies, a drop in Alloprevotella ( Wang J. et al, 2020 ; Wu et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ; Hao et al, 2022 ; Liu et al, 2022 ) and an increase in Blautia ( Zhao et al, 2021 ; Bao et al, 2022 ) and Tyzzerella ( Li et al, 2022 ) are found in animal models of in insulin resistance or glucose intolerance. On the other hand, antidiabetic medications and bioactive compounds modulate the gut microbial community of diabetic mouse model, characterized by increased Alistipes ( Hu et al, 2019 ; Jeong et al, 2021 ; Li et al, 2021 ; Wu R. et al, 2022 ) and decreased Anaerotruncus ( Yong et al, 2022 ), Oscillibacter ( Lin et al, 2022 ; Wang et al, 2022 ), Allobaculum ( Jia et al, 2017 ; Shen et al, 2021 ; Xu et al, 2021 ; Ma et al, 2022 ), Acetatifactor ( Wu Y. et al, 2022 ) and Turicibacter ( Zhao et al, 2021 ). These findings coincide with the correlation between microbiota and metabolic phenotypes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to published studies, a drop in Alloprevotella ( Wang J. et al, 2020 ; Wu et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ; Hao et al, 2022 ; Liu et al, 2022 ) and an increase in Blautia ( Zhao et al, 2021 ; Bao et al, 2022 ) and Tyzzerella ( Li et al, 2022 ) are found in animal models of in insulin resistance or glucose intolerance. On the other hand, antidiabetic medications and bioactive compounds modulate the gut microbial community of diabetic mouse model, characterized by increased Alistipes ( Hu et al, 2019 ; Jeong et al, 2021 ; Li et al, 2021 ; Wu R. et al, 2022 ) and decreased Anaerotruncus ( Yong et al, 2022 ), Oscillibacter ( Lin et al, 2022 ; Wang et al, 2022 ), Allobaculum ( Jia et al, 2017 ; Shen et al, 2021 ; Xu et al, 2021 ; Ma et al, 2022 ), Acetatifactor ( Wu Y. et al, 2022 ) and Turicibacter ( Zhao et al, 2021 ). These findings coincide with the correlation between microbiota and metabolic phenotypes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of experimental diabetes, the species and number of beneficial bacteria were significantly lower, while pathogenic bacteria were significantly higher [17].In this study,we found that PTR significantly upregulated the abundance of Muribaculum, norank_f__Muribaculaceae, and Parabacteroides in db/db mice while significantly reducing the abundance of the harmful bacterium Desulfovibrio. A study has demonstrated that Plukenetia volubilis L. leaf significantly increased Muribaculum abundance in db/db mice, a beneficial bacterium that can improve inflammation, dyslipidemia, and glucose intolerance [18][19].Norank_f_Muribaculaceae was a beneficial dominant bacterium in the mouse intestine and was negatively correlated with the glucose levels of postprandial blood [20]. Parabacteroides is a beneficial bacterium that significantly improves insulin resistance and has been shown in vitro to activate the intestinal gluconeogenic pathway through the conversion of succinate, thereby exerting a hypoglycaemic effect [21].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of experimental diabetes, the species and number of beneficial bacteria were significantly lower, while pathogenic bacteria were significantly higher [23]. A study has demonstrated that the Plukenetia volubilis L. leaf significantly increased Muribaculum abundance in db/db mice, a beneficial bacterium that can improve inflammation, dyslipidemia, and glucose intolerance [24,25]. In this study, we found that PTR significantly upregulated the abundance of Muribaculum, Norank_f_Muribaculaceae, and Parabacteroides in db/db mice, while significantly reducing the abundance of the harmful bacterium Desulfovibrio.…”
Section: Discussionmentioning
confidence: 99%